Christ, creation, and the cosmic goal of redemption a study of Pauline creation theology as read by Irenaeus and applied to ecotheology - Johnson Leese, J. J. (London Bloomsbury Publishing PLC, 2018)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Acknowledgements -- Abbreviations -- Chapter 1 Introduction and Background to Study -- I. The Aims of the Study -- II. The Scholarly Context -- a. Creation in the Old Testament -- b. Creation in the New Testament -- c. Paul and Creation -- d. The Bible and Ecotheology -- III. Methods and Sources -- IV. Chapter Outlines -- a. Chapter 2: 'Christ of the New Creation' -- b. Chapter 3: 'Christ of the Beginning and End' -- c. Chapter 4: 'Christ as Image of God and as Adam' -- d. Chapter 5: 'Irenaeus of Lyons, Theologian of Creation' -- e. Chapter 6: 'Irenaeus and Paul' -- f. Chapter 7: 'Paul, Irenaeus and Ecotheology: Possibilities for Consideration' -- Chapter 2 Christ of the New Creation -- I. New Creation within a Pauline Theological Framework: The Debate -- a. J. Louis Martyn: New Creation as a Cosmic Act of God in Christ -- b. M. Hubbard: New Creation as Personal Conversion -- 1. Internal Spiritual Conversion of Human Hearts -- 2. Paul's Defence of His Apostolic Ministry -- 3. Paul's Own Conversion -- c. T. Ryan Jackson: New Creation as Inclusive of Personal, Communal and Cosmic Dimensions -- d. A Comparative Analysis: Methodological Considerations -- 1. Isaiah or Aseneth? -- 2. Personal Conversion or Apocalyptic Unveiling? -- II. An Apocalyptic Paul? Revisiting the Scholarly Debate -- a. Definitions and Characteristics of Apocalyptic Eschatology -- b. The Linguistic Web of Apocalyptic Motifs in Paul -- 1. ἀποκάλυψις -- 2. αἰών -- 3. καταργέω -- 4. ἐν τάχει -- 5. κόσμος -- 6. κτίσις/ κτίζω153 -- c. Preliminary Conclusions -- III. Conclusion: The Scope of New Creation - Humanity, Community and/or Cosmos? -- Chapter 3 Christ of the Beginning and End -- I. Christ and the Creation of All Things (1 Cor. 8.6 and 1 Cor. 10.26) -- a. Introduction -- b. Background and Context
1. Background Issues (1 Cor. 8.1-11.1) -- 2. The Historical and Social Setting (1 Cor. 8.1-11.1) -- c. First Corinthians 8.6: Introduction and Guiding Questions -- 1. Semantic Sphere of Reference -- 2. Syntactical, Linguistic and Contextual Issues -- (i) First pair of clauses: ἡμῖν εἷς Θεὸς ὁ πατὴρ . . . καὶ εἷς κύριος 'Ιησοῦς Χριστός -- (ii) Second pair of clauses: ἐξ οὗ τὰ πάντα . . . δι' οὗ τὰ πάντα. -- (iii) Third pair of clauses: ἡμεῖς εἰς αὐτόν . . . ἡμεῖς δι' αὐτοῦ -- d. First Corinthians 10.26: Ps. 24.1 (LXX, Ps. 23.1) -- e. Ethical Imperative: Life in the Law of Christ -- II. Christ and the Telos: Subjection and Reconciliation of All Things (1 Cor. 15.20-28) -- III. Implications and Conclusion -- Chapter 4 Christ as Image of God and as Adam -- I. Introduction -- II. Image of God in Primal Creation: Divine Likeness in the Creation Narrative (Gen. 1.26-28) -- III. Image of God in Paul: Introduction to Paul's Reading of Gen. 1.26-28 -- a. Man as Image and Glory of God (1 Cor. 11.2-16) -- b. Humanity as Bearing the Image of the Earthy First-Born Man (1 Cor. 15.47-49) -- c. Christ as Image of God (2 Cor. 4.3-4 -- Col. 1.15) -- 1. 2 Corinthians 4.3-4 -- 2. Colossians 1.15 (Col. 1.9-23) -- d. Believers as in the Image of Christ (Rom. 8.28-30 -- 1 Cor. 15.49 -- 2 Cor. 3.18 -- Col. 3.9-10) -- 1. Romans 8.28-30 -- 2. 1 Corinthians 15.49 -- 3. 2 Corinthians 3.18 -- 4. Colossians 3.9-10 -- e. Preliminary Conclusions -- IV. Adam and Christ: The New Creation in Christ Illuminates the First Creation in Adam (1 Cor. 15.21-22 -- 1 Cor. 15.42-49) -- V. Conclusions -- Chapter 5 Irenaeus of Lyons, Theologian of Creation -- I. Introduction -- a. Scholarship on Irenaeus and Creation -- b. Background and Setting of Irenaeus -- c. 'Gnostic' Teaching on the Creator, Creation and Redemption -- II. The Irenaean Response
a. Pillar One: The Integrity and Unity of God Who Creates through His Two Hands, Son and Spirit -- 1. The Motivating Principle of Creation -- 2. Creation Ex Nihilo -- b. Pillar Two: The Integrity of the Incarnation -- 1. Incarnation and Protology: Mediating God to Creation -- 2. Incarnation as Material and Spiritual: The Humanitas and Divinitas of Christ -- i. Incarnation as human: Adam as a 'type' of Christ -- ii. Incarnation and the goodness of creation -- iii. Incarnation and the Eucharist -- 3. Incarnation and Soteriology -- i. Soteriology as the redemption of sin: the redirection of human free will towards God -- ii. Soteriology as the redemption and immortality of the flesh -- iii. Soteriology as the perfecting of all things -- c. Pillar Three: The Climax of Creation in the Economy of God -- 1. A Modified Chiliastic Vision -- i. The inheritance of the earth -- ii. Participation with God: a theocentric climax -- III. Conclusion -- Chapter 6 Irenaeus and Paul -- I. Hermeneutical and Exegetical Conventions -- a. Background and Current Scholarship on Irenaeus' Reading of Paul -- b. The Prolegomena to the Hermeneutical Task -- 1. Establishing Authoritative Texts: The Unity and Harmony of the New with the Old -- 2. Establishing Epistemological Limitations on Human Knowledge -- 3. Establishing the Rule of Faith as the Basis for Community Reading -- II. Irenaeus' Ktisiological Framework: The Pauline Texts -- a. Christ and Creation: A Pauline Framework -- 1. Christ and Creation: Protology -- 2. Christ and Creation: The Incarnation -- 3. Christ and Creation: Soteriology and Eschatology -- III. Conclusion -- Chapter 7 Paul, Irenaeus and Ecotheology: Possibilities for Consideration -- I. Pauline Creation Themes and Ecotheology -- II. Ecological Hermeneutic Considerations -- a. A Christocentric Theological Hermeneutic
b. Beyond Rom. 8.19-25 and Col. 1.15-20 -- c. Ecology as a Hermeneutical Lens -- III. Pauline Theological Categories -- a. Soteriology: Redemption to Creation and Telos -- b. Incarnation and Eucharist in Relation to the Creation -- c. Theocentric Directed Eschatology -- IV. Conclusion: In the Beginning ... in the New Beginning 'in Christ' -- Bibliography -- Index
Includes bibliographical references and index. Description based on print version record
Keywords: Irenaeus; Electronic books; Bible; Epistles of Paul; Theology; Irenaeus -- Saint, Bishop of Lyon; Creation -- Biblical teaching; Ecotheology; Hochschulschrift